Is the sound environment relevant for how people use common spaces?. Issue 4 (December 2018) - Estévez-Mauriz, Laura; Forssén, Jens; Dohmen, Maud E
Rapid and intrusive spatial adjustments in common spaces are increasingly questioned by the awareness of citizens demanding higher quality standards. This study aims to understand the use of common space by identifying how the sound environment affects the functions of space and the interaction with other environmental and spatial variables. Is there a certain sound environment required or that should be avoided when designing a space for a specific activity? In situ evaluations with regular users were collected in nine common spaces in Gothenburg, Sweden, conducting sound recordings and questionnaires. Site selection responded to the purpose of the analysed places, the noise level (LAeq) of the city road traffic noise map, and the number of activities suggested by the city sociotope maps. The analyses revealed that certain activities could be identified from LAeq values. Discriminant functions with respect to sound levels primarily identified a tranquil/restorative vibrant dimension, where the highest noise levels tend to be at the most vibrant end. Other results showed that a considerable variability of overall and visual quality judgements came from the variability in sites. These quality assessments were highly correlated, allowing both to be analysed as a single attribute. The variability in sound quality was much lower. Notable is the difference between recorded and perceived loudness. In addition, poor sound quality judgement does not seem to correlate with the perception of mechanical sources as the main source of noise.